2017
DOI: 10.1002/chem.201704837
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Discrimination through 1H NMR and Luminescence Spectroscopy: Dynamic Processes and Solid Strip for Chiral Recognition

Abstract: The appropriate choice of the host molecules with well-defined optical activity (S-H/R-H) helps in the differentiation between two secondary ammonium ion-derivative guest molecules with different optical activities (R-G/S-G) based on the fluorescence resonance energy transfer (FRET)-based luminescence responses. Crown ether-based host molecules with opposite chiral configurations (R-H, S-H) have been derived from 1,1'-bi-2-naphthol (BINOL) derivatives that have axially chiral biaryl centers. These chiral crown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 87 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…In the cases of ( R )‐ 18 , ( S )‐ 18 , ( R )‐ 19 , ( S )‐ 19 , ( R,R )‐ 20 , and ( S,S )‐ 20 , association constants ( K ) were given only for the formation of ( R )‐( R ) and ( S )‐( S ) complexes showing large fluorescence spectral changes . In the cases of ( R )‐ 17 and ( S )‐ 17 , the complex stability constants ( K ) were determined by isothermal titration calorimetry …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the cases of ( R )‐ 18 , ( S )‐ 18 , ( R )‐ 19 , ( S )‐ 19 , ( R,R )‐ 20 , and ( S,S )‐ 20 , association constants ( K ) were given only for the formation of ( R )‐( R ) and ( S )‐( S ) complexes showing large fluorescence spectral changes . In the cases of ( R )‐ 17 and ( S )‐ 17 , the complex stability constants ( K ) were determined by isothermal titration calorimetry …”
Section: Discussionmentioning
confidence: 99%
“…Gangopadhyay et al reported binaphtho‐crown ethers ( R )‐ 17 and ( S )‐ 17 (Figure ) . Functionalization of 1‐phenylethylamines with an anthracene fluorophore furnished such guest molecules, the enantiomers of PhEtAnt·PF 6 (Figure ), of which differentiation by crown hosts ( R )‐ 17 and ( S )‐ 17 could be examined on the basis of Förster resonance energy transfer (FRET)‐based fluorescence responses.…”
Section: Discussionmentioning
confidence: 99%
“…The approach that was used in the present work can be considered as the initial point to use chiral perylene bisimide (PBI) based systems for the detection of specific chiral form. The supramolecular chiral discrimination of a single enantiomer over the other is reported even for other systems (Cooper et al, 2017;Gangopadhyay et al, 2017;Noguchi et al, 2017). We present here the symmetric PBI with D-phenylalanine in the amide position which acts as a chiral sensor only for the D form of the phenylalanine.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, BINOL has been extensively used in chiral recognition [13] and exhibit excellent chiral induction in asymmetric reactions [14]. In recent years many scientists have employed this chiral molecule to create a new group of receptors, which have turned out to be appropriate for effective chiral recognition of anions [15,16,17], cations [18,19] and neutral molecules [20,21].…”
Section: Introductionmentioning
confidence: 99%